TJS 2016
DOI: 10.15547/tjs.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Complications of multiple pregnancies. Overwiew

Abstract: Multiple gestations are high risk pregnancies which may be complicated by prematurity,low birthweight, preeclampsia, anaemia, postpartum haemorrhage, intrauterine growth restriction, neonatal morbidity and high neonatal and infant mortality. Preterm labor and birth represent the greatest risk to a multiple pregnancy. Sixty percent of multiples are born prematurely (<37 weeks) compared to about 10% of singleton pregnancies. Placental function is more likely to be abnormal in a multiple pregnancy. Another placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In 1994 Querleu and Leblanc created a precedent of surgical staging procedure for patients with ovarian or fallopian tube malignancies by using laparoscopic technique [ 5 ]. In the area of gynecologic oncology, laparoscopic surgery had been widely accepted by more and more surgeons and patients due to its advantage of minimal trauma and rapid recovery [ 17 , 18 ]. However, its application still remained controversial because of the unpleasant complications such as the unexpected tumor rapture or spillage, instrumental thermal injury, difficulty in tumor extraction and port-site metastasis etc., which were of enormous importance to patients’ prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1994 Querleu and Leblanc created a precedent of surgical staging procedure for patients with ovarian or fallopian tube malignancies by using laparoscopic technique [ 5 ]. In the area of gynecologic oncology, laparoscopic surgery had been widely accepted by more and more surgeons and patients due to its advantage of minimal trauma and rapid recovery [ 17 , 18 ]. However, its application still remained controversial because of the unpleasant complications such as the unexpected tumor rapture or spillage, instrumental thermal injury, difficulty in tumor extraction and port-site metastasis etc., which were of enormous importance to patients’ prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplegestation pregnancies are associated with preterm birth. 6,7 More than 90% of multiples are born preterm compared with 6% to 10% of singletons, 2,8 and very preterm birth is especially high for pregnancies with triplets and higher-order multiples when compared with singleton pregnancies. 9 In turn, preterm birth is associated with complications that have individual, family, societal, and financial implications.…”
mentioning
confidence: 99%
“…9 In turn, preterm birth is associated with complications that have individual, family, societal, and financial implications. 10,11 In previous work, researchers evaluated outcomes of triplets 6, 12 -15 and reported higher risks of mortality, 2 respiratory distress syndrome, 3,7,8,12 retinopathy of prematurity (ROP), 3,16 and intraventricular hemorrhage (IVH) 3,7 in triplets who were very preterm than in singletons. However, authors of other studies reported no difference in outcomes between triplets and singletons.…”
mentioning
confidence: 99%
“…Maternal complications include cardiovascular risk, metabolic disorders, preeclampsia, placental abruption, urinary tract infection, and preterm delivery. [ 8 ] Fetal complications include prematurity, intrauterine growth retardation, congenital anomalies, and twin-to-twin transfusion syndrome. [ 9 ] Neonatal complications and outcomes include neonatal death, prematurity, low birth weight, respiratory distress, hypocalcemia, and hypoglycemia, which increase compared to singleton pregnancies.…”
Section: Introductionmentioning
confidence: 99%